The Impact of Post-Retirement Social Relationship Changes on Depressive Symptoms in Chinese Older Adults: The Mediating Role of Loneliness and Moderating Role of Social Networks - Fu S; Zhang G (Psychology Research and Behavior Management)
Shuangle Fu,1,2 Ge Zhang1 1School of Elderly Care Services and Management, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, People’s Republic of China; 2School of Aging Industry, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Shuangle Fu, School of Elderly Care Services and Management, Nanjing University of Chinese Medicine, No. 138, Xianlin Road, Qixia District, Nanjing, Jiangsu Province, 210023, People’s Republic of China, Tel +86 152 5189 6029, Email hdsgfsl1101@126.comPurpose: Depressive symptoms are an important issue among older adults that can affect their mental health and quality of life. This study examined the impact of post-retirement social relationship changes on depressive symptoms, and the mediating role of loneliness and the moderating role of social networks among Chinese older adults.Patients and Methods: The participants were 1260 retired older adults from the 2018 China Longitudinal Aging Social Survey. The study conducted mediation and moderation analyses with an ordinary least squares (OLS) regression model and employed the Karlson, Holm, and Breen (KHB) method to further analyze the mediating role of loneliness.Results: Post-retirement social relationship changes exhibited significant a positive association with depressive symptoms and loneliness, while social networks demonstrated a significant negative association with depressive symptoms. The older adults experiencing post-retirement social relationship substantial changes were more vulnerable to developing depressive symptoms. Furthermore, loneliness mediated the association between post-retirement social relationship changes and depressive symptoms, whereas social networks moderated this association.Conclusion: The findings elucidate the association between post-retirement social relationship changes and depressive symptoms among Chinese older adults, highlighting the roles of loneliness and social networks. It underscores that taking a rational view of retirement-related changes and maintaining and expanding social networks may reduce the effects of post-retirement social relationship changes on depressive symptoms.Keywords: post-retirement social relationship changes, depressive symptoms, loneliness, social networks, older adults